2010
DOI: 10.32607/20758251-2010-2-4-72-81
|View full text |Cite
|
Sign up to set email alerts
|

Classification of G-Quadruplex DNA on the Basis of the Quadruplex Twist Angle and Planarity of G-Quartets

Abstract: The present work is devoted to the analysis of the G-quadruplex DNA structure using the bioinformatics method. The interest towards quadruplex DNAs is determined by their involvement in the functioning of telomeres and onco-promoters as well as by the possibility to create on their basis aptamers and nanostructures. Here, we present an algorithm for a general analysis of the polymorphism of the G-quadruplex structure from the data bank PDB using original parameters. 74 structures were grouped according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 52 publications
6
27
0
Order By: Relevance
“…The G-quartets are spaced by 3.4 Å (S7 Table), leading to optimal π-π base stacking interactions. The average intramolecular helical twist between G-quartets within each GQ monomer is 29 ± 4˚for T1 and 28 ± 1˚for T7 (S8 Table), consistent with values reported for parallel GQs [39,41] and calculated for the parallel Tel22-NMM structure (29 ± 1˚) [30]. The two monomers are twisted with respect to each other by 116 ± 1˚, 117 ± 2˚(S9 Table), and 120 ± 3˚, for T1, T7 and Tel22, respectively.…”
Section: Plos Onesupporting
confidence: 85%
“…The G-quartets are spaced by 3.4 Å (S7 Table), leading to optimal π-π base stacking interactions. The average intramolecular helical twist between G-quartets within each GQ monomer is 29 ± 4˚for T1 and 28 ± 1˚for T7 (S8 Table), consistent with values reported for parallel GQs [39,41] and calculated for the parallel Tel22-NMM structure (29 ± 1˚) [30]. The two monomers are twisted with respect to each other by 116 ± 1˚, 117 ± 2˚(S9 Table), and 120 ± 3˚, for T1, T7 and Tel22, respectively.…”
Section: Plos Onesupporting
confidence: 85%
“…Successful stabilization from the cations has reportedly maintained an average interquartet distance of 3.3 Å between the bipyramidal antiprism that is formed. 83 Zheng and co-workers 85 have shown that single-strand G-rich sequence can fold into a G-quadruplex with very low K + -ion concentration (0.01–01 mM), indicating strong binding of K + . To look into this feature, distance calculations were performed to define some parameters of the K + cations relative to the surrounding G4 DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of thrombin, 15 TBA aptamers are in an equilibrium between two states: a complex with the nanotube and a quadruplex structure (which is a four stranded DNA helix that acts to stabilize aptamer molecules; for the DNA aptamer in question, it was previously described by R.V. Reshetnikov and one of the authors of this work in [10]). Basically, the equilib rium is shifted towards the DNA-nanotube complex, but when the aptamer is able form a complex with thrombin, the conformation equilibrium becomes shifted towards the quadruplex structure, which has much smaller contacts with the nanotube.…”
Section: Resultsmentioning
confidence: 88%